FRI0050 Tocilizumab achieves better repair of focal bone erosions than tumour necrosis factor inhibition in ra patients – data from the prospective rebone study on erosion repair. (12th June 2018) - Schett, G.; Finzel, S.; Kraus, S.; Regensburger, A.; Kocijan, R.; Rech, J.
Abstract : Background: Focal bone erosions are considered as markers for irreversible structural damage in patients with rheumatoid arthritis (RA). Several studies have suggested that limited repair of focal bone erosion can occur but no study has so far compared the effect of different biological disease modifying anti-rheumatic drugs (bDMARDS) on erosion repair. Objectives: To compare focal bone erosion repair in RA patients treated with interleukin-6 receptor inhibitor (tocilizumab, TOC) with patients receiving tumour necrosis factor inhibitors (TNFi) Methods: Prospective non-randomised observational study in 66 erosive RA patients with active disease (DAS28-ESR>3.2) and inadequate response to methotrexate receiving treatment with TOC monotherapy (n=33) or TNFi in combination with methotrexate (n=33) for 52 weeks. Patients received high-resolution peripheral quantitative computed tomography (HR-pQCT) of the MCP and wrist joints of the dominant hand at baseline and after 52 weeks. Volume (in mm3) of the largest ("sentinel") erosion in the MCP joints and in the wrist was assessed by two readers blinded for treatments and for the sequence of the images. Demographic (sex, age, body mass index, smoking, Charlson comorbidity index) and disease specific parameters (disease duration, ACPA and RF status) were assessed at baseline and activity scores (DAS28, SDAI, CDAI, HAQ) at baseline and every three months thereafter. Results: Groups were balanced for age, sex, BMI and comorbidities as well as disease duration, disease activity, functional state, autoantibody status and bone damage at baseline. TOC (DAS28-ESR: baseline: 6.2±0.5; 52wk: 2.3±1.0) and TNFi (DAS28-ESR: baseline: 6.3±0.6; 52wk: 2.8±1.2) significantly reduced disease activity to a similar extent, achieving DAS28 remission in 22/33 and 19/33 patients, respectively, after 52 weeks. Volumes of the sentinel erosions significantly decreased in the MCP joints of TOC patients (−1.0±1.1 mm3), while remaining stable in TNFi treated patients (−0.05±0.9 mm3) (TOC vs. TNFi: p<0.001). Similar effects were observed in the wrist (TOC: −2.9±5.6 mm 3 ; −0.08±4.1 mm 3 ) with significant differences between the two groups (p=0.0017). Erosion repair was particularly frequent in RA patients reaching fast remission within the first 3 months of treatment. Y axis shows the volume of the sentinel erosion at baseline (black circles) and 52 weeks follow-up (red squares), x-axis the patient numbers (n=33) Conclusions: The REBONE study shows that TOC has higher efficacy than TNFi to repair existing bone erosions in patients with RA. In contrast, the effects of TOC and TNFi on the inflammatory symptoms of RA are comparable. These data suggest that IL-6 is the central factor for the disturbed homeostasis between bone resorption and bone formation in the joints of RA patients. Acknowledgements: The RE-BONE study was supported by Chugai Pharmaceutical Co., Ltd. Disclosure of Interest: None declared